2019
DOI: 10.3390/jmse7070200
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Weighted Multi-Discriminator CycleGAN for Underwater Image Enhancement

Abstract: In this paper, we propose a novel underwater image enhancement method. Typical deep learning models for underwater image enhancement are trained by paired synthetic dataset. Therefore, these models are mostly effective for synthetic image enhancement but less so for real-world images. In contrast, cycle-consistent generative adversarial networks (CycleGAN) can be trained with unpaired dataset. However, performance of the CycleGAN is highly dependent upon the dataset, thus it may generate unrealistic images wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In certain cases, Cycle-GAN models could also introduce undesired effects. Jaihyun et al find that performance of CycleGAN is highly dependent on the dataset, potentially resulting in unrealistic images with less information content than the original images 34 . Finally, because real domain data is being used in both domain adaptation paradigms, adjustments to the real data target domain, e. g., use of a different C-arm X-ray imaging device or design changes to surgical hardware, may require de novo acquisition of real data and re-training of the models.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, Cycle-GAN models could also introduce undesired effects. Jaihyun et al find that performance of CycleGAN is highly dependent on the dataset, potentially resulting in unrealistic images with less information content than the original images 34 . Finally, because real domain data is being used in both domain adaptation paradigms, adjustments to the real data target domain, e. g., use of a different C-arm X-ray imaging device or design changes to surgical hardware, may require de novo acquisition of real data and re-training of the models.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to more project specific tasks, the standard data augmentation method cannot generate images that are close to the preferred real-world data, and it requires a significant amount of time and trial and error to produce the desired results. Therefore, DL models such as Generative Adversarial Networks (GANs), CycleGAN, and U-Nets are the current state-of-theart methods used to augment datasets and increase their size [18][19][20]. GAN are mainly used to produce synthetic images that follow the same probability distribution as the real images.…”
Section: Related Workmentioning
confidence: 99%
“…solve this problem by using a 'cycle consistency loss' that allows learning the mutual mappings between two domains from unpaired data. Such models have been effectively used for unpaired learning of perceptual image enhancement [53,54] as well. Furthermore, Ignatov et al [55] showed that additional lossterms for preserving the image-based content and texture information improve the performance of image quality enhancement using GANs.…”
Section: Automatic Image Enhancementmentioning
confidence: 99%